Cyclooxygenase-2 (COX2) gene polymorphisms and the risk of sporadic colorectal cancer and polyps among Jordanian population - Shomaf, Maha; Yousef, AL-Motassem; Ababna, Nidaa; Bobali, Yahya (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Cyclooxygenase-2 (COX2) is a crucial enzyme involved in the metabolism of Prostaglandins and it has been implicated in several processes. This study was done to investigate the associations of polymorphisms in COX2 gene with the risk of colorectal cancer or polyps development among Jordanian population and to correlate with other ethnicities. Materials and Methods: One hundred and thirty five cases (135) of colorectal carcinoma were studied for COX2 −A1195G polymorphisms employing PCR-RFLP technique, in addition to 104 cases of adenomatous polyps and 115 matched controls taken from the general population. Results: Sixty eight colorectal cancer patients were males and 67 of patients were females with a median age of (58.0±13.9 year). Sixty six (66) of polyp cases were males and 38 were females with a median age of (58.1±14.16). The A-1195G AA carriers were 3.1 times less likely to develop CRC (95% CI: 1.8-5.3, p<0.0001), and 1.8 times less likely to develop polyps (95% CI: 0.99-3.2, p=0.056).The A-1195G AG carriers were at higher risk to develop cancer in a dose dependent manner. The AG carriers were 2.9 time more likely to develop CRC and two times more likely to develop polyps when compared to controls. The A allele was more predominant in controls than in polyps or CRC cases. Carriers of the A allele were 1.6 times less likely to develop polyps and 2.6 times less likely to develop CRC. Conclusion: The presence of the COX-2 -1195AA genotype may protect against risk of developing colorectal cancer.